Proceedings of the 3rd Meeting of the Association of Ground Stone Tools Research - Pedersen, Patrick,; Jörgensen-Lindahl, Anne,; Sørrensen, Mikkel,; Richter, Tobias, (Archaeopress Publishing Ltd, 2022)
The papers in this volume focus especially on the relationship between ground stone artefacts and foodways and include archaeological and ethnographic case studies ranging from the Palaeolithic to the current era, and geographically from Africa to Europe and Asia.